Role of nutrition in patients with coexisting chronic obstructive pulmonary disease and sarcopenia - Nan, Yayun; Zhou, Yuting; Dai, Ziyu; Yan, Ting; Zhong, Pingping; Zhang, Fufeng; Chen, Qiong; Peng, Linlin (Frontiers in Nutrition, 2023)
Chronic obstructive pulmonary disease (COPD) is one of the most common chronic diseases in the elderly population and is characterized by persistent respiratory symptoms and airflow obstruction. During COPD progression, a variety of pulmonary and extrapulmonary complications develop, with sarcopenia being one of the most common extrapulmonary complications. Factors that contribute to the pathogenesis of coexisting COPD and sarcopenia include systemic inflammation, hypoxia, hypercapnia, oxidative stress, protein metabolic imbalance, and myocyte mitochondrial dysfunction. These factors, individually or in concert, affect muscle function, resulting in decreased muscle mass and strength. The occurrence of sarcopenia severely affects the quality of life of patients with COPD, resulting in increased readmission rates, longer hospital admission, and higher mortality. In recent years, studies have found that oral supplementation with protein, micronutrients, fat, or a combination of nutritional supplements can improve the muscle strength and physical performance of these patients; some studies have also elucidated the possible underlying mechanisms. This review aimed to elucidate the role of nutrition among patients with coexisting COPD and sarcopenia.